Biological Properties of Streptococcal Cell-Wall Particles I. Determinants of the Chronic Nodular Lesion of Connective Tissue - Schwab, John H. (1965)
Schwab, John H. (University of North Carolina, Chapel Hill). Biological properties of streptococcal cell-wall particles. I. Determinants of the chronic nodular lesion of connective tissue. J. Bacteriol. 90:1405–1411. 1965.—The capacity of cell-wall fragments to induce a chronic remittent nodular lesion after a single injection into rabbit skin varies qualitatively as well as quantitatively among the streptococci. This variation among strains is the result of a summation of several properties of the bacterial cell, some intrinsic and others extrinsic to the cell-wall structure. With some species, the inability to produce this lesion may be related to the susceptibility of cell walls to lysozyme. Other factors defined in this paper include production of hyaluronidase, and association of the cell walls with a component which can affect the interval between injection and appearance of the nodules, called the latent time. Separation of cell-wall fragments from more soluble cell material by centrifugation results in a shorter latent time. Addition of the soluble supernatant fraction back to the cell walls prolongs the latent time and increases the area of lesion involvement. This latter effect is due to a spreading factor present in most cell extracts. Addition of hyaluronidase to isolated cell-wall fragments duplicates the increased lesion area but tends to shorten further the latent time. Thus, the soluble cell extract contains both a spreading factor and a component which prolongs the latent time, and the final influence on the lesion is in part a product of these two activities. The ease and extent of mechanical disintegration of the cell wall can also vary widely among strains and yield cell extracts differing in their content of cell-wall fragments of optimal size.